Identifying the enemy civilian participation in armed conflict - Crawford, Emily (Oxford University Press, 2015)
Civilians are increasingly playing crucial roles in the conduct of military operations. This book looks at different forms of civilian participation in armed conflict, examining the pressure this disruptive practice places on the traditional laws of war